Carnitine palmitoyltransferase 1C promotes EMT-associated cisplatin resistance in non-small cell lung cancer cells - Renjie Chen; Jiahui Wang; Shuoyu Huang; Xuefeng Hu; Xinran He; Tiange Zhang; Yunhan Hu; Huijun Wei; Sihui Nian; Yushu Huang; Zhihao Wu (Cancer Biology & Medicine)
Objective: Lung cancer is the most common cause of cancer-related deaths worldwide. Platinum-based chemotherapy is one of the main treatment options for patients with non-small cell lung cancer (NSCLC) but the effectiveness of chemotherapy is encumbered by drug resistance. Therefore, understanding the molecular mechanisms underlying chemotherapy resistance is crucial in improving treatment outcomes and prognosis. Methods: The cell viability assay and apoptosis were used to analyze chemoresistance. Western blot analysis and wound healing testing were used to evaluate the epithelial-to-mesenchymal transition (EMT). Immunoprecipitation was used for analysis of protein modification. Promoter activity was determined using the luciferase reporter assay. Immunofluorescence staining was used to determine reactive oxygen species levels. The expression patterns of EMT markers and carnitine palmitoyltransferase 1C (CPT1C) were determined by Western blot analysis. Results: CPT1C, which was shown to be highly expressed in lung cancer, is associated with cisplatin resistance in NSCLC cells. CPT1C depletion increased NSCLC cell sensitivity to cisplatin, while overexpression of CPT1C increased NSCLC cell resistance to cisplatin. Induction of EMT mediated CPT1C-induced cisplatin resistance. Ectopic expression of Snail reversed the increase in cisplatin sensitivity triggered by CPT1C knockdown. Moreover, CPT1C was shown to be regulated at the post-translational level and an E3-ubiquitin ligase, NEDD4L, was shown to be a major regulator of CPT1C stability and activity. Conclusions: These data provide evidence for the first time that the lipid metabolism enzyme, CPT1C, mediates resistance to chemotherapy. Therefore, the use of combination therapy with a CPT1C inhibitor may be a promising new avenue in lung cancer treatment.